Effect of Different Doses of Cerium Oxide Nanoparticles (CeO2 NPs) on In vitro Maturation, Cleavage and Embryo Development of Buffalo Oocytes - Hamed, Shrouk H.; Abd-Allah, Saber; EL-Baghdady, Yehia R.; El-Shahat, Khaled (Journal of Buffalo Science, 2026)
The present study investigated the effects of different concentrations of cerium oxide nanoparticles (CeO2 NPs) on viability, in vitro maturation (IVM), fertilization (IVF), and subsequent embryo development of buffalo oocytes. Cumulus-oocyte complexes (COCs) were collected from slaughtered female buffalo and cultured in IVM medium. COCs were incubated in an in vitro maturation (IVM) medium supplemented with different concentrations of cerium oxide nanoparticles (CeO2 NPs) (10, 20, and 100µg/ml), alongside an untreated control group(0), for 22-24 hours under controlled conditions (39 °C, 5% CO2, and 95% relative humidity). At 0, 8, and 24 hours of incubation, oocytes from all experimental groups were collected, and their viability was determined using the trypan blue exclusion method. Following maturation, oocytes from both control and CeO2 NPs -treated groups were subsequently used for in vitro fertilization with frozen-thawed buffalo spermatozoa. The gametes were co-cultured for an additional 24 hours at 39°C in 5% CO2, following the protocol. Fertilization success was initially determined by the appearance of a second polar body and further verified by cleavage to the two-cell stage. The viability of developing embryos was assessed using the trypan blue exclusion method. The results demonstrated that supplementation of the IVM medium with 20 µg/ml CeO2 NPs significantly enhanced nuclear maturation of oocytes, yielding the highest value (95%) compared with the control and other treated groups. Moreover, the development of fertilized oocytes, as evidenced by the progression into the two-cell stage, was significantly higher at the 20 µg/ml concentration (85%) than in the other treatments. Additionally, the percentage of non-developed (degenerated) zygotes was significantly reduced at this concentration, with the lowest value recorded (15%). In conclusion, the addition of 20 µg/ml cerium oxide nanoparticles to the IVM medium appears to improve the in vitro developmental competence of buffalo oocytes.